Иннакей Кельда (1902-1994): [очерк / автор очерка Вячеслав Ар-Серги] - Ар-Серги Вячеслав Витальевич (Библиотека "Известия Удмуртской Республики", 2009)
Экземпляры: ф.1 (2011) / Инвентарный номер: 53672 / Сис.шифр: 83.3(2Рос=Удм) / Авт.знак: А 79 / ГРНТИ: 17.01 / ББК: 83.3(2Рос=Удм)6^VLBC/PL